2019
DOI: 10.1097/ans.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Knowing

Abstract: Fundamental patterns of knowing in nursing have historically served to clarify the substance and structure of the discipline, significantly contributing to nursing's body of knowledge. In this article, we continue the scholarly conversation on patterns of knowing in nursing by advancing spiritual knowing as a pattern of knowing that helps advance nursing's agenda toward universal well-being and critical during this time toward interdisciplinarity. Implications for nursing are explored in relation to enduring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
12
0
4
Order By: Relevance
“…Confidence and competence relate to clinical activities that enhance patients' physical and mental wellbeing. That nurses are not always comfortable extending their reach to spiritual care has been the focus of research by Willis and Leone-Sheehan (2019), who found that nurses consistently reported feeling unprepared to address issues of spirituality despite their acknowledgment of the necessity of addressing the spiritual in holistic care of patients.…”
Section: Holistic Carementioning
confidence: 99%
“…Confidence and competence relate to clinical activities that enhance patients' physical and mental wellbeing. That nurses are not always comfortable extending their reach to spiritual care has been the focus of research by Willis and Leone-Sheehan (2019), who found that nurses consistently reported feeling unprepared to address issues of spirituality despite their acknowledgment of the necessity of addressing the spiritual in holistic care of patients.…”
Section: Holistic Carementioning
confidence: 99%
“…At the same time as the policy summit, an article was published in Advances in Nursing Science titled “Spiritual Knowing: Another Pattern of Knowing in the Discipline” (Willis & Leone-Sheehan, 2019). Much of this article involved nursing theory development and the role fundamental patterns of knowing in nursing have “historically served to clarify the substance and structure of the discipline, significantly contributing to nursing’s body of knowledge” (p. 58).…”
mentioning
confidence: 99%
“…Willis and Leone-Sheehan (2019) described various patterns of knowing from nursing theorists such as Carper (1978), Meleis and Trangenstein (1994), Newman, Sime, and Corcoran-Perry (1991), and Chinn and Kramer (2011). Nursing embraces multiple ways of knowing as evidenced by each noted theory.…”
mentioning
confidence: 99%
See 2 more Smart Citations